La0.8Sr0.2MnO3-d-based nanocomposite functional layers for improved cathode efficiency in SOFCs - Caizán-Juanarena, Leire; Zamudio-García, Javier; Porras-Vázquez, José Manuel; Ramírez-Losilla, Enrique; Marrero-López, David (My University, 2022)
Solid Oxide Fuel Cells (SOFC) are efficient electrochemical devices that are able to convert chemical energy in the form of fuels into electricity, but at low operating temperatures they are mainly limited by the high polarization resistance of the cathode. This way, optimizing the electrode microstructure and incorporating functional layers have proven to be useful to improve electrode properties. The present work proposes the incorporation of several nanocomposite functional layers by spray-pyrolisis at the La0.8Sr0.2MnO3-d (LSM) cathod, by combining different ionic conductors, i.e. LSM-Ce0.9Gd0.1O1.95 (CGO) and LSM-Bi1.5Y0.5O3 (BYO). These exhibited lower grain size compared to that of the homologous single phase; specially the LSM-CGO nanocomposite showed improved adherence to the electrolyte without the presence of any crack or delamination after annealing at 1000 ºC. The incorporation of functional layers also reduced the Area Specific Resistance (ASR) values of the cathode and the full cell with LSM-CGO as functional layer revealed higher power densities than the cell with no functional layer.
Keywords: Combustibles; Materiales nanocompuestos; Electroquímica; Cátodos; Electroquímica -- Aparatos e instrumentos; LSM cathode; Solid oxide fue cells; Nanocomposites; Functional layers